Koncepcja i skutki finansowe wprowadzenia podatku dochodowego w gospodarstwach rolniczych - Wasilewski, Mirosław; Gruziel, Kinga (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2007)
The paper presents a concept of replacing the agricultural tax with the income tax in farms of agricultural type “field cultivation”. The agricultural tax has been regarded as insufficient concerning differences in farms’ effectiveness. Implementation of the income tax in farms would result in a higher charge. The charge would be the highest in the largest farms, where the agricultural tax takes about 11–12% of the income tax amount. However, implementation of tax concessions and tax allowances would significantly decrease charges in farms. Including costs of a farmer’s family employment, in large farms only (about 93 ha AL) would appear an income to be taxed. On the other hand, a problem of saving appropriate revenues from the income tax to a local government’s budget has been still unsolved.